2011
DOI: 10.3892/ijo.2011.1312
|View full text |Cite
|
Sign up to set email alerts
|

Gene alterations in the PI3K/PTEN/AKT pathway as a mechanism of drug-resistance (Review)

Abstract: Abstract. The most common therapeutic approach for many cancers is chemotherapy. However, many patients relapse after treatment due to the development of chemoresistance. Recently, targeted therapies represent novel approaches to destroy cancer cells. The PI3K/PTEN/AKT pathway is a key signaling pathway involved in the regulation of cell growth. Dysregulated signaling of this pathway may be associated with activating mutations of PI3K-related genes. Analyses of these mutations reveal that they increase the PI3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
52
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(52 citation statements)
references
References 30 publications
0
52
0
Order By: Relevance
“…Evidence from in-vitro and in-vivo models suggests that PI3K-AKT activation is associated with decreased sensitivity to several chemotherapeutic agents and radiotherapy [3, 7]. Additionally, clinical reports highlight the route of resistance to EGFR and HER2 targeted agents, Cetuximab and Trastuzumab (Herceptin), as being reversible upon PI3K-AKT inhibition [98, 99].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Evidence from in-vitro and in-vivo models suggests that PI3K-AKT activation is associated with decreased sensitivity to several chemotherapeutic agents and radiotherapy [3, 7]. Additionally, clinical reports highlight the route of resistance to EGFR and HER2 targeted agents, Cetuximab and Trastuzumab (Herceptin), as being reversible upon PI3K-AKT inhibition [98, 99].…”
Section: Discussionmentioning
confidence: 99%
“…Alteration of upstream pathway components, such as activating mutations in RAS, PI3K or loss of PTEN, can be the primary oncogenic event leading to therapeutic failure[2, 6]. However, it is the activation of AKT that is proposed to modulate cell death responses to therapeutic agents and mediate resistance [3, 7]. Not surprisingly, the aim of regaining sensitivity to various therapies has focused attention on targeting the PI3K-AKT pathway [8].…”
Section: Introductionmentioning
confidence: 99%
“…Because of its role in cell proliferation and survival, alterations in the PI3K-AKT pathway have been described in various cancers [4]. In addition to its contribution to cancer development and progression, aberrant PI3K-AKT signaling is involved in resistance to various chemotherapeutic agents [5]. PI3K class I A molecules, the only members of this kinase family involved in cancer, consist of a heterodimer comprised of the p110 catalytic and p85 regulatory subunits [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…The PI3KCA gene has been found to be amplified and overexpressed in several types of cancers. It has been suggested that the point mutations that activate the PI3KCA gene may represent a novel mechanism for the induction oncogenic PI3K signaling pathway [14, 15]. Hafsi et al [15] stressed the fact that oncogenic PI3KCA mutations play a critical role in human malignancies and provide evidence that kinases with cancer-specific mutations such as PI3K may be ideal targets for small-molecule specific inhibitors that would create the opportunity to develop new anticancer drugs [15].…”
Section: Introductionmentioning
confidence: 99%
“…It has been suggested that the point mutations that activate the PI3KCA gene may represent a novel mechanism for the induction oncogenic PI3K signaling pathway [14, 15]. Hafsi et al [15] stressed the fact that oncogenic PI3KCA mutations play a critical role in human malignancies and provide evidence that kinases with cancer-specific mutations such as PI3K may be ideal targets for small-molecule specific inhibitors that would create the opportunity to develop new anticancer drugs [15]. PI3KCA gene mutations have been found in several cancers (e.g., liver, breast, colorectal, brain, and gastric) and the majority of these have been shown constitutively to activate the protein's catalytic subunit [16, 17].…”
Section: Introductionmentioning
confidence: 99%